The Lifecycle and Effective Communication of CSR to the Stakeholder and the Public - Habib, Ahsan; J, Sr. Marlene Mucha, S.S. (International Journal of Economics, Business and Management Studies, 2018)
The lifecycle of CSR focuses on the essential needs of an effective communication with the prospective stakeholders, as well as the public. The topic will include the explanation of the CSR definition and the vigorous growth of the CSR. This paper will focus on the detailed description of the importance of the CSR transparency that will maintain a good reputation. Furthermore, a global example, such as UN, will be used to explain the tremendous growth of CSR in various sectors. An in-depth research has been used to clarify the importance of the CSR program through an effective communication.